'No one in our family ever went to college': Parents' orientations towards their children's post-secondary education and future occupations. (2019) - Scanlon, Margaret; Powell, Fred; Leahy, Pat; Jenkinson, Hilary; Byrne, Olive
Highlights: Parental orientations to children's post-secondary education and future are explored. Generational changes in attitudes to school completion and access to HE and FE. All parents valued education and thought it had become more important over time. Varying levels of parental engagement in children's education and decision-making. Information on post-secondary education needs to be more accessible to parents. Abstract: This article presents an analysis of parents' expectations and aspirations regarding their children's education and future occupations. Drawing on interviews with parents from disadvantaged communities in Ireland, we consider parents' perceptions of the value of education (particularly further and higher education), and how they see their own role in relation to their children's education and future plans. Our findings suggest that parents valued education as a means of securing a 'good job' and wanted their children to progress further in the educational system than they had. At the same time, there were notable variations in the manner of parental engagement with their children's education and decision-making. Our findings are considered in the context of debates on social class and education.